Evaluation of the influence of factors on CTDIvol and CNR in CT-Scan thorax procedures - Sari, Nadhia Nortania; Fendriani, Yoza; Pujaningsih, Febri Berthalita (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study investigates the effect of exposure parameter variations in CT-Scan on image quality and radiation dose during thoracic examinations. The exposure parameters analyzed were tube voltages of 80, 100, and 120 kV, along with tube currents of 100, 200, and 300 mA. A quantitative approach was employed using a Cannon TOS air phantom at the Radiology Department of Bhayangkara Hospital Jambi with a Toshiba 16-slice CT-Scan unit. Radiation dose was obtained from CTDIvol  values displayed on the CT console, while image quality was evaluated using the Contrast to Noise Ratio (CNR) calculated with RadiAnt DICOM Viewer software. The research method included obtaining the Computed Tomography Dose Index volume (CTDIvol) directly from the scanner console for each exposure setting, while the Contrast-to-Noise Ratio (CNR) was calculated by measuring the mean intensity of the region of interest (ROI) on the phantom and the standard deviation of the background area to quantify image contrast relative to noise. The findings demonstrate that both tube voltage and current strongly influence CTDIvol and CNR. Higher exposure settings increased radiation dose, with several combinations exceeding the recommended safety threshold. At 100 mA, all tube voltages remained below the BAPETEN regulatory limit of 11 mGy for non-contrast thoracic scans. Similarly, 200 mA at 80 and 100 kV remained within safe limits, while 200 mA at 120 kV slightly exceeded the threshold. Doses rose markedly at 300 mA, particularly at 120 kV, reaching values far above the permissible limit.